Ethiopia Public Expenditure Review - World Bank Group (World Bank, Washington, DC, 2016)
Ethiopia’s remarkable socio-economic transformation over the last decade has been marked by: a reorientation of expenditure from recurrent to capital; a significant devolution of resources from Federal Government to Regions; and a clear prioritization of infrastructure spending, while protecting spending on education at four percent of GDP. The Government of Ethiopia has also leveraged external resources to boost spending in pro-poor sectors, particularly health and social protection. As a result, Ethiopia is home to the largest social safety net program in Africa, and has also achieved remarkable health outcomes using cost effective approaches. Recent investments have seen a significant build-up of capital stock, with capital spending at sector level pointing towards increased service capacity. The current public investment-led strategy requires to be complemented by increased budgetary provisions in operations and maintenance so that new investments translate into enhanced service coverage and delivery. As Ethiopia lays the foundation to become a middle income country, and the changing global environment implies declining external assistance, it is imperative that domestic taxation activity support this transition. The current tax-to-GDP ratio is low compared to peer countries, and the tax structure would benefit from increased contributions by direct tax sources. Therefore, there is an immediate need for advancing tax reforms and improve capacity and quality of tax administration. Broadening the tax bases, through review of exemptions, as well as review of tax rates might be venues to consider. Additional revenues will create the much-needed fiscal space to increase funding for operations and maintenance for service delivery, and support fiscal sustainability. As a follow-up to this Public Expenditure Review, the Government of Ethiopia has asked the World Bank to provide further analytical support, with a view to enhance domestic revenue mobilization through simpler and more efficient taxation, while retaining equity priorities in public finances.